Bounds of Some Topological Indices of the Cartesian Product of F-sum Graphs - B., Chandrakala S.; Roshini, G. R.; Sooryanarayana, B. (Journal of Informatics and Mathematical Sciences, 2019)
Lower and upper bounds of Randic index(R), sum-connectivity index (SCI), arithmetic geometric index (AG1), Harmonic index (H) and multiplicative indices of Cartesian productof F-sum of connected graphs are obtained.